Effects of Soluble Corn Fiber Alone or in Synbiotic Combination with Lactobacillus rhamnosus GG and the Pilus-Deficient Derivative GG-PB12 on Fecal Microbiota, Metabolism, and Markers of Immune Function: A Randomized, Double-Blind, Placebo-Controlled, Crossover Study in Healthy Elderly (Saimes Study) - Costabile, Adele; Bergillos-Meca, Triana; Rasinkangas, Pia; Korpela, Katri; de Vos, Willem M.; Gibson, Glenn R. (Frontiers in Immunology, 2017)
Background The aging process leads to a potential decline in immune function and adversely affects the gut microbiota. To date, many in vitro and in vivo studies focused on the application of synbiotics (prebiotics combined with probiotics) as a promising dietary approach to affect gut microbiota composition and improved functioning of the immune system. However, studies using synbiotic preparations often have the limitation that it remains unclear whether any effect observed is a result of the prebiotic or probiotic or a synergistic effect of the combined supplement. Objectives We investigated the effects of a probiotic Lactobacillus rhamnosus GG and pilus-deficient L. rhamnosus GG-PB12 combined with Promitor™ Soluble Corn Fiber (SCF, a candidate prebiotic) on fecal microbiota, metabolism, immunity, and blood lipids in healthy elderly persons. A prospective, double-blind, placebo controlled, randomized, single-centered, crossover study in 40 healthy elderly subjects (aged 60–80 years) was carried out. Volunteers were randomized to consume either probiotic and prebiotic as synbiotic, prebiotic or placebo (maltodextrin) during 3 weeks. Three-week washout periods separated all the treatments. We assessed effects upon blood lipids, glucose, cytokines, natural killer (NK) cell activity, phenotype, and intestinal microbiota composition. SCF decreased IL-6, which was not observed with the synbiotics. Results Consumption of L. rhamnosus GG combined with SCF increased NK cell activity compared to baseline in females and the older group. In the fecal microbiota analyses, the strongest community shifts were due to L. rhamnosus GG combined with SCF and SCF treatments. L. rhamnosus GG combined with SCF and L. rhamnosus GG-PB12 combined with SCF significantly increased the genus Parabacteroides. L. rhamnosus GG combined with SCF and SCF increased concentrations of Ruminococcaceae Incertae Sedis. Oscillospira and Desulfovibrio slightly decreased in the L. rhamnosus GG combined with SCF group, whereas Desulfovibrio decreased also in the L. rhamnosus GG-PB12 combined with SCF group. L. rhamnosus GG combined with SCF reduced total cholesterol and LDL-cholesterol in volunteers with initially elevated concentrations. C-reactive protein significantly decreased during L. rhamnosus GG-PB12 combined with SCF intervention compared to baseline. Conclusion In conclusion, the synbiotic combination of L. rhamnosus GG with SCF showed a tendency to promote innate immunity by increasing NK cell activity in elderly women and in 70 to 80-year-old volunteers and decreased TC and LDL-c in hypercholesterolemic patients. In addition, L. rhamnosus GG-PB12 combined with SCF demonstrated an increase in NK cell activity compared to SCF alone in older volunteers. We also found significant positive effects on the immune response, evidenced by a decrease of the pro-inflammatory cytokine IL-6. Therefore, dietary intervention with L. rhamnosus GG combined with SCF could be of importance in elderly as an attractive option for enhancement of both the microbial and immune systems.